Reduced‐order modeling for the control of selective noncatalytic reduction of nitrogen monoxide. Issue 3 (30th October 2015) - Farcy, Benjamin; Vervisch, Luc; Domingo, Pascale; Perret, Nicolas
Abstract : The design of a reduced‐order model is discussed to help in the control of selective noncatalytic reduction (SNCR) of nitrogen monoxide. Instead of relying on a look‐up table of nominal operating points, it is proposed to solve for the time evolution of a set of stochastic particles interacting through a model for turbulent mixing and a reduced chemistry. Each particle is representative of a fraction of the mass flowing in the system in gaseous or liquid form. To calibrate and validate the reduced‐order model, which runs in a few minutes on a desktop computer, reference three‐dimensional and unsteady large‐eddy simulation is performed in the complex geometry of a real incinerator. This is done solving the full set of conservation equations of mass, momentum, and energy over a 162 million cells mesh. The results confirm the possibility of real‐time SNCR optimization from the solving of partial differential equations. © 2015 American Institute of Chemical Engineers AIChE J, 62: 928–938, 2016